Monetary policy of the European Central Bank : BVAR Approach - Vykoukal, Daniel; Pokorný, Tomáš; Slaný, Martin, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This thesis investigates the effectiveness of monetary policy conducted by the European Central Bank, with a particular focus on comparing conventional and unconventional monetary policy. The thesis employs a BVAR model, which sign restrictions are partly derived from a New Keynesian DSGE framework. The findings indicate that conventional monetary policy of interest rates is characterized by an immediate and sharp impact on both inflation and output, aligning well with theoretical expectations and confirming its effectiveness in normal economic conditions. Unconventional monetary policy via asset purchases, on the other hand, exhibits a more gradual and delayed response but still positively affects macroeconomic variables over time. The empirical findings confirm that quantitative easing, as an unconventional policy tool, is capable of stabilizing output and inflation, particularly during periods when conventional monetary policy is constrained.
Vedoucí práce: Tomáš Pokorný
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses